Managing the Quality of Islamic Religious Education in Muslim-Minority Contexts: Evidence from Southern Thailand - Muhammad Wamae; Ikhrom Ikhrom; Fatkurroji Fatkurroji (Journal of Counseling, Education and Society, 2026)
This study aims to analyze the management of quality improvement in Islamic Religious Education learning at Ma'had Al-Bi'that Ad-Diniah Yala and Prasan Wittaya Mulniti Pattani, Southern Thailand, focusing on implementation processes, supporting and inhibiting factors, and strategic challenges in maintaining educational quality within a Muslim minority context. Employing a qualitative approach with a multi-case study design, data were collected through semi-structured interviews, document analysis, and participatory observations involving school leaders, teachers, and relevant stakeholders. The findings reveal that quality improvement management is implemented through an integrated cycle consisting of participatory planning, instructional implementation, comprehensive evaluation, and continuous improvement initiatives. The planning process involves institutional leaders, academic coordinators, teachers, and foundation representatives by integrating the Thai national curriculum with Islamic religious curricula and the educational needs of Muslim minority communities. The implementation of learning emphasizes the integration of Islamic knowledge, character formation, and adaptive pedagogical strategies, including the use of digital learning resources. Evaluation practices function not merely as administrative procedures but as mechanisms for instructional refinement through teacher development, curriculum revision, and collaborative improvement. The study further identifies visionary leadership, teacher commitment, organizational collaboration, and community support as key enabling factors, while financial limitations, digital competency gaps, technological infrastructure constraints, and curriculum adaptation pressures represent major challenges. The findings demonstrate that Islamic education quality improvement in minority contexts is a process of institutional adaptation that negotiates religious identity, national educational demands, and digital transformation. This study contributes to the broader discourse on Islamic educational management by proposing an adaptive quality governance perspective for sustaining the relevance and resilience of Islamic schools in plural and rapidly changing societies.